On growth and form of animal behavior - Ilan Golani; Neri Kafkafi (Frontiers in Integrative Neuroscience)
In this study we propose an architecture (bauplan) for the growth and form of behavior in vertebrates and arthropods. We show in what sense behavior is an extension of anatomy. Then we show that movement-based behavior shares linearity and modularity with the skeletal body plan, and with the Hox genes; that it mirrors the geometry of the physical environment; and that it reveals the animal’s understanding of the animate and physical situation, with implications for perception, attention, emotion, and primordial cognition. First we define the primitives of movement in relational terms, as in comparative anatomy, yielding homological primitives. Then we define modules, generative rules and the architectural plan of behavior in terms of these primitives. In this way we expose the homology of behaviors, and establish a rigorous trans-phyletic comparative discipline of the morphogenesis of movement-based behavior. In morphogenesis, behavior builds up and narrows incessantly according to strict geometric rules. The same rules apply in moment-to-moment behavior, in ontogenesis, and partly also in phylogenesis. We demonstrate these rules in development, in neurological recovery, with drugs (dopamine-stimulated striatal modulation), in stressful situations, in locomotor behavior, and partly also in human pathology. The buildup of movement culminates in free, undistracted, exuberant behavior. It is observed in play, in superior animals during agonistic interactions, and in humans in higher states of functioning. Geometrization promotes the study of genetics, anatomy, and behavior within one and the same discipline. The geometrical bauplan portrays both already evolved dimensions, and prospective dimensional constraints on evolutionary behavioral innovations.